BIMBINGAN DAN KONSELING DENGAN PENDEKATAN RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK PENERIMA MANFAAT - Muhamad Abdul Kohar; Imam Mujahid (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
This article describes the concept of guidance and counseling rational emotive behavior therapy (REBT) Islamic to increase the resilience of prostitutes. REBT is an approach that directive, the approach to reeducation counselees to understand the cognitive input that causes emotional disturbance, trying to change the thought patterns counselee to let the irrational thoughts or study anticipates the benefits or consequences of behavior. Resilience is the ability of individuals to adapt, so as to put themselves well against an unpleasant experience. Islamic REBT approach focuses on thinking (aqliyah) rational individual to the nature of the individual who escorted counselees aware that he is a servant and vicegerent of Allah in order to survive counselees his life in this world and hereafter. Islamic REBT counseling techniques are affective, cognitive, and behavioral adapted to the conditions of the counselee. Such techniques include: Assertive adaptive, Reinforcement, Social and Assertive modeling exercise.